(untitled) (Medico Legal Update, 2021)
Background: Legionella have emerged as a pathogenic group due to increased use and poor maintenance of artificial water environments. World Health Organization considers Legionella associated diseases to be underestimated, especially in developing countries due to difficulty in detection. The aim of this study was isolation and culture of Legionella spp. from artificial water systems and to test the importance of iron concentration which can be developed as a reliable chemical marker. Method: Thirty samples each were collected from drinking water coolers, cooling towers and shower heads fitted in different houses of Mangaluru city. Isolation and identification of the bacteria were carried out as per the standard protocols followed by determination of iron content prescribed by IS 3025 (Part 53). Conclusion: Our study shows that concentrations of iron, is an important factor that increases the likelihood of Legionella spp. Statistically, a concentration of 300 mg Fe/L shows a positive correlation with Legionella presence. Therefore, monitoring suspect sites for iron concentration and chelation of available iron, can be developed as respective assays for identifying Legionella spp. Furthermore, we show that PCR based detection of Legionella is a more robust method than the classical 3-plate method, especially for virulent strains.